Design and implementation of a parabolic trough collector system - Bilgin, Egemen Orhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
With the effect of global warming on weather, most countries are interested in renewable energy sources and solar energy is the most promising one among others with an endless source. With this awareness, a lab scale test setup with an existing parabolic trough solar collector was designed and implemented with the aim of measuring inlet and outlet temperatures from the collector to calculate the thermal efficiency, useful heat gain, heat loss, and optical efficiency. A boiler was used as thermal storage with its two coils inside. Also, a solar tracking system was put into practice to follow the movement of the Sun to decrease the angle of incidence. The experiments were performed at Boğaziçi University Renewable Energy Technologies Laboratory on Sarıtepe Campus. As a result of experiments, maximum temperature and maximum thermal efficiency are found to be 65.25°C at 3.20 P.M. and 14.5% at 3:30 P.M. Moreover, the transition and turbulent flow are observed in the receiver at around 60°C.
Keywords: Solar thermal energy.; Parabolic troughs.